2014
DOI: 10.17017/jfish.v2i3.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Farming of giant freshwater prawn (Macrobrachium rosenbergii) in Bagerhat, Bangladesh

Abstract: The study was carried out to know the present status of Macrobrachium rosenbergii culture in Bagerhat district, Bangladesh from March 2012 to January 2013. Education levels of farmers were found as illiterate (12.3%), primary (36.19%), secondary (20%), SSC (13.33%), HSC (12.38%) and graduate (5.71%). M. rosenbergii culture was the primary and secondary occupation of 80% and 20% farmers respectively. Average stocking density and production in extensive, improved extensive and semi-intensive culture were 9609, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…After interviewing with the farmers, it was found that most of the farmers (53%) were illiterate, while 13% had primary education, 27% had secondary education and 7% had higher education (Figure 5). In the present study, 66% of the farmers acquired below SSC level of education due to poor education facilities, which was similar to Akter et al (2014), who reported that 68% of the farmers acquired below SSC level education in Bagerhat district and also reported that the farmers were educated below SSC level (Akter et al, 2014).…”
Section: 2 Educationsupporting
confidence: 86%
See 2 more Smart Citations
“…After interviewing with the farmers, it was found that most of the farmers (53%) were illiterate, while 13% had primary education, 27% had secondary education and 7% had higher education (Figure 5). In the present study, 66% of the farmers acquired below SSC level of education due to poor education facilities, which was similar to Akter et al (2014), who reported that 68% of the farmers acquired below SSC level education in Bagerhat district and also reported that the farmers were educated below SSC level (Akter et al, 2014).…”
Section: 2 Educationsupporting
confidence: 86%
“…According to Ahmed et al (2008), prawn farmers practiced a stocking density of 19,830-21,155 PL/ha. Average stocking densities of PL varied in extensive, improved extensive and semiintensive culture systems at 9,609, 11,502 and 22,847 PL/ha, respectively (Akter et al, 2014). Alam et al (2007), and Barmon et al (2007) also reported the average stocking densities of prawn to be 1,500-15,000 PL/ha and 7,411-39,520 PL/ha, respectively.…”
Section: Stocking Densitymentioning
confidence: 97%
See 1 more Smart Citation
“…Una de las enfermedades más comunes son las manchas negras causadas frecuentemente por bacterias que atacan la cutícula (Johnson y Bueno, 2000). En Bangladesh, la enfermedad de la mancha negra o de la branquia negra es la más común desde que siembran las PL's hasta la cosecha, causando mortalidades masivas y las mayores pérdidas económicas (Akter et al, 2014).…”
Section: Discussionunclassified
“…Due to the excellences of giant freshwater prawn caused vivid giant freshwater prawn culture in some countries in Southeast Asia, South Asia, and North Australia. Nowadays, giant freshwater prawn culture is massively developed in various countries, such as in United States of America and China (Akter et al, 2014;Zafar et al, 2015;David et al, 2018). In 2009-2012, the production of giant freshwater prawn has contributed over 57.1% of the total production of freshwater prawn Macrobrachium sp.…”
Section: Introductionmentioning
confidence: 99%